Lowering S-Adenosylmethionine Levels in Escherichia coli Modulates C-to-T Transition Mutations - Macintyre, Georgina (American Society for Microbiology, 2001)
Deoxycytosine methylase (Dcm) enzyme activity causes mutagenesis in vitro either directly by enzyme-induced deamination of cytosine to uracil in the absence of the methyl donor, S-adenosylmethionine (SAM), or indirectly through spontaneous deamination of [5-methyl]cytosine to thymine. Using a Lac reversion assay, we investigated the contribution of the first mechanism to Dcm mutagenesis in vivo by lowering the levels of SAM. Escherichia coli SAM levels were lowered by reducing SAM synthetase activity via the introduction of a metK84 allele or by hydrolyzing SAM using the bacteriophage T3 SAM hydrolase. The metK84 strains exhibited increased C-to-T mutagenesis. Expression of the T3 SAM hydrolase gene, under the control of the arabinose-inducible P(BAD) promoter, effectively reduced Dcm-mediated genomic DNA methylation. However, increased mutagenesis was not observed until extremely high arabinose concentrations were used, and genome methylation at Dcm sites was negligible.